Association of Metabolic Factors with Essential Hypertension - Khandaker, N Rahman; Akhtaruzzaman, -; Mahfuz, K Rahat; Khandakar, AR; Khan, MMR; Rahman, M Khalilur (TAJ: Journal of Teachers Association, 2011)
Background-Metabolic syndrome is a risk factor for cardiovascular disease, so it should call attention. South Asian person has preponderance to it. Objectives-The proper findings of metabolic syndrome are a key to prevent cardiovascular disease. Hypertension is a component of metabolic syndrome with which patients are at increased risk for cardiovascular disease. Methods-This study was carried out in cardiology outdoor of Shaheed Suhrawardy medical college hospital, Dhaka. A total of 322 patients were enrolled from January 2008 to December 2010. Metabolic syndrome was defined as three of the followings: (a) Abnormal fasting serum level of glucose (≥110 mg/dl or 6.1 mmol/L), ( b) abdominal obesity (waist circumference >102 cm in men and >88 cm in women), (c) Triglycerides (≥150 mg/dl), (d) High density lipoprotein cholesterol (<40 mg/dl in men and <50 mg/dl in woman), (e) Hypertension, which was common in all patients. Results- Among hypertensive’s patients 31.8% had hyperglycemia, 37.9% had high waist circumference, 69.8% had low HDL cholesterol and 54.3% high triglycerides. As per definition of NCEP-ATP-III, metabolic syndrome had been detected in 17% of male, 37% of female and 27% of the total population. Conclusion- Metabolic factors are a common association in hypertensive cases. These patients are at increased risk of coronary and cerebro-vascular disease and require more vigorous prevention. Furthermore in all hypertensive patients metabolic screening is recommended. TAJ 2011; 24(1): 21-25